2020
DOI: 10.1080/02681102.2020.1727827
|View full text |Cite
|
Sign up to set email alerts
|

Displaced and dismayed: how ICTs are helping refugees and migrants, and how we can do better

Abstract: Employing ICT platforms has the potential to improve efforts to assist displaced people, or to liberate them in being more able to help each other, or both. And while platform development has resulted in a patchwork of initiativesan electronic version of 'letting a thousand flowers bloom'there are patterns emerging as to which flowers grow and have 'staying power' as compared to ones that wilt and die. Using a partial application of grounded theory, we analyze 47 platforms, categorizing the services they provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 30 publications
0
35
0
Order By: Relevance
“…In addition, m-Health applications of AI are more likely to identify atrial fibrillation than routine care (Halcox et al, 2017), and can enable patients to optimize their blood glucose control and reduce stigma associated with hypoglycemic episodes (Lawton et al, 2018). M-Integration applications of AI, in relation to interactivity with host government, availability of education and linguistic resources, communicability with home country, connectedness with public population and accessibility to information, can improve efforts to assist displaced people, or to liberate them in being more able to help each other, or both (Bock et al, 2020, AbuJarour et al, 2019Fernandez-Luque and Imran 2018;Castro and New, 2016). M-Health applications of AI designed for immigrants use natural language processing to enable conversations with users via text message (Castro and New, 2016).…”
Section: M-integration Applications Of Artificial Intelligencementioning
confidence: 99%
“…In addition, m-Health applications of AI are more likely to identify atrial fibrillation than routine care (Halcox et al, 2017), and can enable patients to optimize their blood glucose control and reduce stigma associated with hypoglycemic episodes (Lawton et al, 2018). M-Integration applications of AI, in relation to interactivity with host government, availability of education and linguistic resources, communicability with home country, connectedness with public population and accessibility to information, can improve efforts to assist displaced people, or to liberate them in being more able to help each other, or both (Bock et al, 2020, AbuJarour et al, 2019Fernandez-Luque and Imran 2018;Castro and New, 2016). M-Health applications of AI designed for immigrants use natural language processing to enable conversations with users via text message (Castro and New, 2016).…”
Section: M-integration Applications Of Artificial Intelligencementioning
confidence: 99%
“…DPs are considered fundamental to the transformative changes in the humanitarian sector, for instance. The humanitarian sector is experiencing changes in how displaced people are managed, with DPs such as GPS, WhatsApp, and Facebook, serving as sources of critical information during the journeys of displaced people and migrants (Bock, Haque, and McMahon 2020). Bock, Haque, and McMahon (2020) examined the successes and shortfalls of digital platforms designed for refugees and migrants using 57 semi-structured interviews with stakeholders (people, NGOs in Greece, and the United Nations).…”
Section: Platform Economy and Inclusionmentioning
confidence: 99%
“…The humanitarian sector is experiencing changes in how displaced people are managed, with DPs such as GPS, WhatsApp, and Facebook, serving as sources of critical information during the journeys of displaced people and migrants (Bock, Haque, and McMahon 2020). Bock, Haque, and McMahon (2020) examined the successes and shortfalls of digital platforms designed for refugees and migrants using 57 semi-structured interviews with stakeholders (people, NGOs in Greece, and the United Nations). The authors identified and categorized platforms into eight and found DPs to play a critical role in the processing, connecting, reunification, access to basic but essential social needs and services, as well as integrating refugees and displaced people into host communities (Bock, Haque, and McMahon 2020).…”
Section: Platform Economy and Inclusionmentioning
confidence: 99%
“…As displaced people, they have moved from their homes into new and unfamiliar communities in which they need to adapt and construct meaningful lives (Díaz Andrade and Doolin, 2016). Majority of these studies have focused on the use of mobile phones by refugees and migrants in the global north (Bock et al, 2020;Shah et al, 2019). These studies have shown that mobile phone penetration and use among refugees is growing and can be seen to facilitate the social integration of refugees (Abujarour et al, 2021;Casswell, 2019).…”
Section: Displaced People and Mobile Phonesmentioning
confidence: 99%
“…However, despite the interest in the study of displaced people, research on mobile phones and displaced people has received little attention within the ICT4D domain (Bock et al, 2020). The few existing studies discussed above focused on the role of mobile phones on the social inclusion of refugees and migrants in the global north (Alencar, 2020;Mancini et al, 2019).…”
Section: Displaced People and Mobile Phonesmentioning
confidence: 99%